SINTESIS DAN UJI TOKSISITAS ANALOG FLAVANON TERSUBSTITUSI HALOGEN - Rush, Ibnu; Teruna, Hilwan Yuda; Zamri, Adel (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Flavanones have been reported to possess many of interesting biological activities such as antimicrobe, antitumor, antioxidance, antiinflammatory, antimalaria, anticancer, and anti-HIV. In this research, a halogenated flavanone 2-(3 -bromophenyl)chroman-4-one was synthesized by cyclization of (E)-3-(3-bromophenyl)-1-(2-hydroxyphenyl)-2-propen-1-one using sodium acetate as catalyst under microwave irradiation. The compound showed a good yield, and then was characterized by UV, IR and 1 H-NMR spectroscopy. The toxicity activity of this compound was determined using Brine Shrimp Lethality Test (BSLT) method against larvae Artemia salina Leach and showed a good activity with LC50 = 0,457 µg/mL. The result indicated that this compound was potential as anticancer.